CONCEPTUAL REFORMULATION OF TA'LIM AS A PARADIGM OF ISLAMIC EDUCATION LEARNING IN BUILDING EDUCATIONAL INTERACTIONS THROUGH RAHMANIYYAH PRINCIPLES - Islamy, Mohammad Rindu Fajar; Abdussalam, Aam; Budiyanti, Nurti; Parhan, Muhamad (Al-Fath, 2021)
This article tries to reformulate the concept of ta'lim in the Quran so that it can be one of the solutions in answering the challenges of today's growing era. The civilization of science and technology is influenced by the philosophical schools of positivism, rationalism, and materialism. True according to this school, must come out with an approach to empiric boundaries and logic (secular), where scientific concepts must be measured in a mustard manner. All the truths produced must never reach the truths that are beyond the reach of the empiric. Al-Quran has very different characteristics and extraordinary, both in terms of content, language and systematics. Al-Quran has provided the best solution for all aspects of human life without limits of space and time, especially in the area of education. The pattern of Islamic education, which is seen as underdeveloped from the Western education model, is a challenge for Muslim intellectuals to formulate the concept of ta'lim that can bridge this gap. With the approach of review literature, the results of the study showed that the concept of ta'lim in the Quran if developed further is very closely related to psychological situations and highly interactive educational communication. Inter-relation between ta'lim concepts in this perspective will be able to build a comprehensive and integrative ta'lim concept with the presence of rahmaniyyah principles, so that intellectual generations will be born accompanied by a solid character.